PEMANFAATAN INSTAGRAM SEBAGAI MEDIA DAKWAH DI KALANGAN MAHASISWA KABUPATEN ACEH BARAT - Junaidi Junaidi (SOURCE : Jurnal Ilmu Komunikasi, 2020)
The phenomenon of preaching message content on Instagram is currently a process of changing the use of media in conveying religious messages to the public. Where the use of preaching media previously was more manual (pulpit and recitation forums) in a limited context and only carried out by certain people. However, with the development of information and communication technology today, the use of dakwah media is more modern, able to reach more mad'u and can be done by anyone, especially the younger generation. This research wants to answer about how the use of Instagram among students in West Aceh Regency? This research uses a qualitative descriptive approach, the research data is collected through a process of observation, questionnaires, and in-depth interviews. The results showed, of the 55 respondents studied answered, the use of Instagram is still at the level to show self-existence with personal identity motives. Where uploads on student Instagram accounts in West Aceh are still dominant with personal content. Although they rarely upload da'wah content, some have never even accessed it at all, they often access it on other accounts, accompanied by giving likes on the content. Most of the student Instagram accounts in West Aceh District are linked to other social media accounts, such as Facebook and Twitter. This makes it easy for users to create automatic posts between Instagram and other social media accounts.